THE COUNCIL OF COMMUNICATION: THE “VOICE” OF THE ENTREPRENEURS IN MEXICAN DEMOCRACY (Andamios, Revista de Investigación Social, 2010)
The Council of Communication (CC) is a business organization created in 1959, dedicated to the generation of publicity campaigns whose purpose is to spread entrepreneurial thinking. From a particular context, the alternation of presidential power in 2000, restructuring and launching a series of campaigns in order to influence in the behavior of Mexicans citizens. This article analyzes the campaigns of the CC from its restructuring. It examines in detail its content and the circumstances in which they were generated, with the purpose of showing the important role taken by entrepreneurs in the country’s democracy, taking into account the special relationship they had with the government of President Vicente Fox.
Keywords: Entrepreneurs; media; democracy